Synthesis and Characterization of Doping Modulated Graphene-based Materials for Device Applications - Bhardwaj, Jai Shree (My University, 2026)
The growing demand for sustainable energy solutions necessitates the development of advanced materials for efficient energy generation and storage. Graphene, a two-dimensional carbon material with exceptional electrical, mechanical, and optical properties, emerges as a promising candidate; however, its zero bandgap and limited tunability restrict direct device applications. This work addresses these challenges through controlled doping and process engineering to tailor the electronic properties of graphene-based materials for supercapacitor and photovoltaic applications.
Agarwal, Pratima